New diarylureas and diarylamides possessing acet(benz)amidophenyl scaffold: Design, synthesis, and antiproliferative activity against melanoma cell line - Kim, Hee Jin; Cho, Hye Jung; Kim, Hwan; El-Gamal, Mohammed I.; Oh, Chang-Hyun; Lee, So Ha; Sim, Taebo; Hah, Jung-Mi; Yoo, Kyung Ho (Pergamon Press Ltd., 2012)
A series of new diarylurea and diarylamide derivatives possessing acet(benz)amidophenyl scaffold was synthesized. Their in vitro antiproliferative activity was tested against A375P human melanoma cell line. Compounds 1c,d and 2c,d showed the highest potencies with IC50 values in sub-micromolar scale. In addition, compounds 1b,e,l and 2e,l were more potent than Sorafenib but with IC50 values in micromolar range. Moreover, compound 2c was equipotent to Vemurafenib, and 2d showed higher potency than Vemurafenib against A375P. Molar refractometry calculation and ADME profiling of the highest potent four derivatives 1c,d and 2c,d are also reported. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: DERIVATIVES; DISCOVERY; SORAFENIB; DIAGNOSIS; THERAPY